Thermomigration induced microstructure and property changes in Sn-58Bi solders. (15th March 2019) - Shen, Yu-An; Zhou, Shiqi; Li, Jiahui; Tu, K.N.; Nishikawa, Hiroshi
Abstract: Thermomigration (TM) has become a critical reliability issue in advanced electronic packaging because of Joule heating. A temperature gradient is required to conduct heat away, and only 1 °C of temperature difference across a 10 μm thick microbump produces a temperature gradient of 1000 °C/cm, which can cause TM, especially in low melting eutectic Sn-Bi solder interconnects. We report here that Bi atoms moving from the hot end to the cold end of the temperature gradient, are the dominant diffusing species. Under the assumption of constant volume, the Sn atoms are squeezed by the Bi atoms at the cold end and have to accommodate for the Bi atoms, which makes them move to the hot end. Consequently, the opposing fluxes of Bi and Sn are found to be about the same. Moreover, the growth of Cu-Sn intermetallic compound (IMC) layers at the cold and the hot end were symmetrical, and were unaffected by TM. Additionally, finite-element-method (FEM) simulations showed that the phase separation of Bi and Sn reduced the current crowding regions which affect the electromigration of the eutectic Sn-Bi solder interconnects. Graphical abstract: Unlabelled Image Highlights: The thermomigration behavior in Cu/Sn58Bi/Cu joints is hardly seen, not to mention the process and details. Bi accumulation at the cold end by thermomigration induces a significant Sn-Bi phase separation in the Sn-58Bi solder joints. The growth of Cu-Sn intermetallic compound layers at the cold and hot end was symmetrical, unaffected by thermomigration. The phase separation of Bi and Sn reduces the current crowding regions.